Dos quintais às ruas: estudo de implantação de hortas nos vazios urbanos de João Pessoa como parte da infraestrutura verde urbana - Silva, Lídia Pereira (2016)
This paper is connected to the proposal of transforming unbuilt areas into elements of the green urban infrastructure. It is fully known that the disorderly processes of urban expansion of brazilian medium-sized cities have caused damaged to the periurban natural environment thus causing the supression of green urban areas. Those areas are considered an importante indicator of the quality of life in the cities, due to the several functions they can exert and the benefits they can bring to the urban population, such as the access to better quality food, when destined to farming. Furthermore, the green areas are part of the green infrasctructure of the cities and are also one of the vital elements to the urban sustainability. Therefore, based on these observations, the potential for implementation of vegetable gardens in empty urban spaces as a part of the green urban infrastructure in João Pessoa, Paraíba’s state’s capital, was evaluated. Through the usage of tools like GIS (Geographic Information System), themed maps were developed aiming at providing the necessary information for the classification, in graded scale, of the potential of transformation of urban empty spaces, adapting and using the systematization developed by Sanches (2011). The chosen methodological procedure is guided by the principles of green infrasctructures and defines quantity and quality indicators, with numerical values for each of these evaluation criteria, which are grouped in three distinct categories- ecological group, hydrous group and social group- the arithmetic mean in each group composes the final grade, and the sum of these grades results in the rate of the potential for the transformation of the analysed areas in vegetated spaces. After the application of the methodological procedure and the visitation of the areas with the highest potential for transformation, some propositions were issued in order to enable the implementation of vegetable gardens in these empty urban spaces and, consequently, the bulding of models of sustainable farming production.